SisCOP: um sistema de cadastramento e controle de registro de ocorrências dos Agentes de Portaria do ICET - Santos, Raimundo Carlos Braz dos (Brasil, 2024)
The increasing evolution of technology brings with it the need to transform tasks complex and mechanical processes into something simple through computerization and less effort to be human, initially information technology was seen only as operational routines, however, today it is characterized by great value for providing real-time tools for decision making. This work aimed to develop a web system for managing information for controlling and storing occurrence records for security agentes ordinance of the Institute of Exact Sciences and Technology, which are currently carried out in a manual. The methodology adopted in the research involved a bibliographical survey, proposal initial, construction, usability evaluation, adjustments and implementation. After the evaluation, it was found that the system provided a positive overall view of its organized interface and intuitive, ease of use, efficiency in performing tasks and stability